Development of fluid bed dryer process control module for fluidization and drying of pharmaceutical powder (2022)
As the fluidization of powdered active ingredients is crucial before compressing into desired forms or shapes, the importance of the fluidized bed dryers cannot be overemphasized. Many studies had been carried out to improve the fluidization of particle bed by measuring and controlling process parameters to achieve quality output, but the implementation of these proved cost intensive. This work was focused on developing a control module using conventional low-cost components for monitoring the drying process of fluidized bed dryer. The module was developed following design calculations of parameters required to determine its rated current capacities, and selection of required components. The components used were selected putting in mind cost and durability, without compromising their suitability in achieving the set objectives for the developed control module. Thereafter, a performance test as carried out to ascertain its performance characteristics. From the design calculations, the overall load (current) rating of the module was 13 amperes. Relays, temperature controller and push buttons were major components selected, putting in mind the overall module capacity of 13 amperes. The selected components suitably performed the expected control operations, and the efficiency was over 98%. The control module was able to regulate the drying procedure to achieve a reduced percentage moisture content of 1.4% at 850c drying temperature. The control module performed the expected function at a reduced cost when compared to control units being adopted in the industry for such purpose. Therefore, the module could be further explored for implementation on large scale commercial dryers.